Flipped Classroom Model For EFL/ESL Instruction in Higher Education: A Systematic Literature Review - Dodi Siraj Muamar Zain (National Research University Higher School of Economics, 2022)
Background. Researchers and teaching practitioners are working on formulating instructional approaches that suit the students' interests by incorporating the latest technology. The flipped classroom model emerges as an alternative to extend the classroom interaction, create a different atmosphere, and accommodate a meaningful and collaborative interaction in the class. Purpose. This paper aims to present a systematic review of past studies focusing on the implementation of the flipped classroom for EFL/ESL instruction in higher education. Methods. A total of 29 articles were selected using specific criteria comprising year and types of publication, contexts, and the determined quality standard. The collected articles were then analyzed to reveal the research components including the research designs, participants, and instructional tools. Results. This study presents a discussion of the practical instructional benefits of the flipped classroom model and the possible barriers. Implications. Furthermore, from this discussion, this study formulated pedagogical and research implications for possible directions in future studies.